Kritik Terhadap Presiden ditinjau dari Perspektif Kebebasan Berpendapat - Dharmawan, Achmad Adhi; Riyantina, Dila; Milda, Osa; Saputra, M. Laskar Ando; Firdaus, M. Faqih (Legalita, 2023)
The purpose of this research is to examine criticism of the President from the perspective of freedom of expression. One of the main ways of realizing the fundamental democratic ideals of freedom of expression in a democratic system is through criticism of political leaders. This study investigates how public opinion, government policies, and political dynamics are affected by presidential criticism. Document analysis, surveys, and interviews with members of different social groups activists, political party members, and the general public are part of the methodology of this study. The data collected was analyzed to determine the trend of public criticism of the President and how these views are shaped by their opinions on freedom of expression. Some respondents felt that the President's right to freedom of expression was upheld, while others felt there were considerable limitations. Public opinion is heavily influenced by criticism of the president, and policy changes may be brought about by such criticism. The study also emphasizes the difficulties and dangers of the right to freedom of expression when the President is criticized. The study also emphasized the importance of traditional and social media to enable the President to take action and convey different viewpoints. The findings of this study highlight the importance of maintaining free speech to preserve the democratic process and provide insights into how democracy works. The findings have important consequences for our understanding of how, in contemporary democracies, criticism of political leaders and free speech interact. The findings of this study add to the body of knowledge on democracy and freedom of expression while providing a useful framework for policymakers and advocates of change.